Economic Challenges of Spain’s Aging Population - Riestra, Jorge Alfonso; Miskolczi, Martina; Hon, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The ageing of the population in Spain poses important economic challenges, especially with regard to the sustainability of the pension system. This thesis explores the multiple impacts of demographic changes on the Spanish pension system and labor market, analyzing historical trends, current challenges and future projections. Through a comprehensive review of demographic data, labor market conditions and pension system structures, this study identifies key areas for policy intervention. The research highlights the need for integrated policies that address demographic trends, improve labor market conditions and ensure the sustainability of pensions. The findings suggest that increasing legal immigration, improving labor market participation and reforming the pension system are critical steps to mitigate the economic impact of population ageing. This study contributes to ongoing policy discussions by providing practical insights and strategic recommendations aimed at maintaining economic stability and social welfare in Spain.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses